Mengkaji Peran Lingkungan Kerja Dan Beban Kerja Terhadap Kepua-san Kerja Karyawan - Andi Tenriolle; Marcelinus Yanto; Halim, Firmansyah (Jurnal Ilmiah Bongaya, 2024)
The purpose of this research is to test and analyze the variables that have the most dominant influence on work environment variables and workload on employee job satisfaction variables, where this research uses a quantitative approach with the research population of employees at PT. Citrasulawesi Sejahtera has 150 employees. And a sample of 60 respondents used the SPSS application for linear regression analysis. The findings obtained in this research explain that the work environment has a positive and significant impact on employee job satisfaction at PT. Citrasulawesi Sejahtera, workload has a significant positive effect on employee job satisfaction seen at PT. Citrasulawesi Sejahtera, while the one that has the biggest influence on job satisfaction from the two independent variables is the work environment variable because it has a significant weakness in terms of job satisfaction.